2014
DOI: 10.1007/s00705-014-2192-2
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of baicalin against influenza A (H1N1/H3N2) virus in cell culture and in mice and its inhibition of neuraminidase

Abstract: Scutellaria baicalensis Georgi, a Chinese herbal decoction, has been used for the treatment of the common cold, fever and influenza virus infections. In previous studies, we found that oral administration of baicalein resulted in the inhibition of influenza A virus replication in vivo, which was linked to baicalin in serum. However, the effective dose and underlying mechanisms of the efficacy of baicalin against influenza A virus have not been fully elucidated. In this study, the antiviral effects of baicalin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 27 publications
1
75
0
Order By: Relevance
“…Baicalin was previously reported to have anti-viral activity [29,30]. In our study, we evaluated the anti-viral activity of baicalin against IAV H3N2 by measuring the virus CPE.…”
Section: Discussionmentioning
confidence: 99%
“…Baicalin was previously reported to have anti-viral activity [29,30]. In our study, we evaluated the anti-viral activity of baicalin against IAV H3N2 by measuring the virus CPE.…”
Section: Discussionmentioning
confidence: 99%
“…Domestic ducks four days old were supplied by Southwest University Laboratory Animal Center (Chongqing, China). Animals were allowed free access to their standard diet and sterile water in a restricted access room with controlled temperature (22)(23)(24)(25)(26) o C), humidity (50-60%), and a 12-hour light/dark cycle in the Laboratory Animal Center of Southwest University (Rongchang, Chongqing, China). The experimental protocol was in accordance with the Guidelines for Animal Experiments of Southwest University and approved by the Institutional Authority for Laboratory Animal Care.…”
Section: Animalsmentioning
confidence: 99%
“…It is generally used to treat oxidative stress, H 2 O 2 -induced cytotoxicity, and collagen-induced arthritis [21][22][23][24]. Contemporary research has shown that baicalin has a positive effect on antibiosis functions [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…It is the main active component of Radix Scutellariae [4] . Baicalin has a wide range of pharmacological effects, which are mainly presented in the antioxidant, free radical scavenging, anti-inflammatory, anti-tumor, blocking calcium channel, inhibiting aldose reductase, antiviral and anti-allergic aspects [5-8] . In addition, baicalin has protective effects on the immune, cardiovascular, digestive and nervous system [9-11] .…”
Section: Introductionmentioning
confidence: 99%